ANALISIS TINGKAT KEBERHASILAN PEMBANGUNAN JARINGAN TELEKOMUNIKASI BERBASIS MIKROTIK PADA SISTEM LAYANAN INTERNET - Delani, Firman; Imansyah , Fitri; Sujaini , Herry (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2025)
Mikrotik Router is a Linux Base operating system that is used as a network router. Mikrotik Router itself is an operating system and software that can be used to turn ordinary computers into reliable network routers, including various features made for IP networks and wireless networks. These features include: Firewall & Nat, Routing, Hotspot, Point to Point Tunneling Protocol, DNS server, DHCP Server, Hotspot, and many other features. By using Mikrotik Groove A-52Hpn (as an Access Point) which has special specifications, apart from being a router it is also integrated with wireless devices that we can directly use as a bridge to the internet network to wireless and use a Solid Parabolic 5GHz 27 dBi antenna as a transmitter and received by Mikrotik Groove 52Hpn (as Client). Mikrotik which is connected from the Governor’s office to the Indonesian Broadcasting Commission Office passes through the Department of Labor and Transmigration Office with a point to point system in order to get an internet connection at a good level so as to facilitate internet access with an average speed of 717.3 Mbps to 911.0 Mbps from the Governor’s Office to the Department of Labor and Transmigration Office with an average speed of 647.1 Mbps to 1061.2 Mbps for the Department of Labor and Transmigration Office to the Indonesian Broadcasting Commission Office